Odpowiedzi

2009-11-22T15:00:14+01:00
√(x + √x) - √(x - √x) = 3/2 √(x przez x + √x).
√(x-√x)²=3/2√(x/x+√x)
x-√x=3/2√(x/x+√x) , podnosimy do²
(x-√x)²=9/4(x/x+√x)²
x²-2x√x+x=9/4x²/(x+√x)²/*(x+√x)²
(x²-2x√x+x)*(x+√x)²=9/4x²


(x²-2x√x+x)*(x²+2x√x+x)-9/4x²=0
x⁴+2x³√x+x³-2x³√x-2x²√x-9/4x²=0
x⁴+x³-2x²√x-9/4x²=0
2009-11-22T15:23:12+01:00
√(x + √x) - √(x - √x) = 3/2 √(x przez x + √x).
√(x-√x)²=3/2√(x/x+√x)
x-√x=3/2√(x/x+√x) | obustronnie do kwadratu
(x-√x)²=9/4(x/x+√x)²
x²-2x√x+x=9/4x²/(x+√x)²/*(x+√x)²
(x²-2x√x+x)*(x+√x)²=9/4x²
(x²-2x√x+x)*(x²+2x√x+x)-9/4x²=0
x⁴+2x³√x+x³-2x³√x-2x²√x
  • Użytkownik Zadane
2009-11-22T15:40:26+01:00
√(x + √x) - √(x - √x) = 3/2 √(x przez x + √x).
√(x-√x)²=3/2√(x/x+√x)
x-√x=3/2√(x/x+√x) , podnosimy do²
(x-√x)²=9/4(x/x+√x)²
x²-2x√x+x=9/4x²/(x+√x)²/*(x+√x)²
(x²-2x√x+x)*(x+√x)²=9/4x²
(x²-2x√x+x)*(x²+2x√x+x)-9/4x²=0
x⁴+2x³√x+x³-2x³√x-2x²√x